Evaluation Information System Success of the PPDB Information System in SMP Negeri 16 Samarinda using DeLone and McLean’s Model - Kusno Harianto; Azahari; Farhan Aufa Azhar (TEPIAN, 2023)
Information System Success Analysis is a structured process of objects, with certain tools, with the aim of knowing whether the information system is successful or not in its application and getting the desired results from the object of research. In this study the data collection methods to be used were questionnaires, interviews, and literature study which were the theoretical foundations to be used. The model to be used is DeLone and McLean with SMP Negeri 16 Samarinda as a case study. With this research using the DeLone and McLean models, it aims to find out how successful the New Student Admissions (PPDB) information system is from the user's point of view, where the users are prospective students and the PPDB committee and whether the PPDB Online information system is very useful or not.